Heterologous vaccination against human tuberculosis modulates antigen‐specific CD4+ T‐cell function. Issue 9 (8th July 2013) - Dintwe, One B.; Day, Cheryl L.; Smit, Erica; Nemes, Elisa; Gray, Clive; Tameris, Michele; McShane, Helen; Mahomed, Hassan; Hanekom, Willem A.; Scriba, Thomas J.
<x xml:space="preserve">Abstract</x> Heterologous prime‐boost strategies hold promise for vaccination against tuberculosis. However, the T‐cell characteristics required for protection are not known. We proposed that boost vaccines should induce long‐lived functional and phenotypic changes to T cells primed by Bacille Calmette Guerin (BCG) and/or natural exposure to mycobacteria. We characterized changes among specific CD4+ T cells after vaccination with the MVA85A vaccine in adults, adolescents, and children. CD4+ T cells identified with Ag85A peptide‐bearing HLA class II tetramers were characterized by flow cytometry. We also measured proliferative potential and cytokine expression of Ag85A‐specific CD4+ T cells. During the effector phase, MVA85A‐induced specific CD4+ T cells coexpressed IFN‐γ and IL‐2, skin homing integrins, and the activation marker CD38. This was followed by contraction and a transition to predominantly IL‐2‐expressing, CD45RA−CCR7+CD27+ or CD45RA+CCR7+CD27+ specific CD4+ T cells. These surface phenotypes were similar to Ag85A‐specific T cells prior to MVA85A. However, functional differences were observed postvaccination: specific proliferative capacity was markedly higher after 6–12 months than before vaccination. Our data suggest that MVA85A vaccination may modulate Ag85A‐specific CD4+ T‐cell function, resulting in greater recall potential. Importantly, surface phenotypes commonly used as proxies for memory T‐cell function did not associate with functional effects of vaccination.